THE INFLUENCE OF EMOTIONS ON LANGUAGE LEARNING (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
This study looks at how emotions affect language learning. Learner’s feelings play an important role in their motivation and ability to use a new language. Positive emotions like confidence and interest help students learn better, while negative emotions such as; fear and anxiety can make learning more difficult. Creating a positive and supportive learning environment is important for improving language skills.